15 years of 106Ru eye plaque dosimetry at Memorial Sloan-Kettering Cancer Center and Weill Cornell Medical Center using radiochromic film in a Solid Water phantom. (17th May 2018) - Trichter, Samuel; Soares, Christopher G; Zaider, Marco; DeWyngaert, J Keith; DeWerd, Larry A; Kleiman, Norman J
Abstract: Purpose . 106 Ru eye plaques are used for treatment of intraocular malignancies, providing a good alternative to enucleation. We perform our own acceptance testing and commissioning of 106 Ru eye plaques using radiochromic film as recommended by ISO standard 21439:2009 'Clinical dosimetry-beta radiation sources for brachytherapy'. A Solid Water 'eye' phantom with several novel features and related tools were developed for accurate radiochromic film dosimetry of eye plaques. Methods . The phantom enables full 3D dosimetric characterization of eye plaques. Films perpendicular to the central axis of the eye plaques are sandwiched between inserts in the phantom. Small holes in the phantom inserts enable marking the films with respect to the eye plaques, assuring exact geometrical co-registration. Special thin unlaminated radiochromic films were utilized, enabling dosimetric measurements virtually at the surface of the eye plaques. Precise film punches were developed in order to cut films with diameters as small as 8.5 mm and make cutouts in films without damaging the cut edges. Results . Full dosimetric characterization of three CCX type and partial characterization of a CIA type 106 Ru eye plaques is presented. Replicate film results were reproducible to within 4%–5%. Even 4% non-uniformities in planar dose rates were easily detected. Comparison with Monte Carlo calculations by Hermida-López 2013 Med. Phys. 40 101705-1–101705-13, found good agreement along the central axis, but some lateral differences. Conclusions. Accurate and precise 106 Ru eye plaque dosimetry was achieved utilizing radiochromic film in the phantom introduced here. Co-registration of eye plaques and films permits not only precise treatment planning calculations along the central axis of the plaque, but also accounts for dosimetric non-uniformities using 2D or 3D methodologies. Dose measurements on the inner surface of the plaques provide precise assessment of the scleral dose, its homogeneity, and the active area of the plaques for coverage determination.